Evaluation of clinical application of multi‐slice computerized tomography in primary retroperitoneal tumors. Issue 5 (27th December 2019) - Feng, Yuanchun; Zhang, Wei; Luo, Chenghua
Abstract: Background: To accurately identify primary retroperitoneal tumors by multi‐slice spiral CT (MSCT) for better treatment. Materials and Methods: The common types of 380 cases of primary retroperitoneal tumor, lesion sites, and MSCT features were compared with pathological results. Fisher's or chi‐square test approaches have been applied in this study. Results: Multi‐slice computerized tomography multi‐directional reconstruction has a high accuracy for primary retroperitoneal tumors (95.7%). Seventy‐three liposarcoma cases were located in peri‐renal space, accounting for 76.8% (13/95) of the tumors in this region. Meanwhile, 65 cases of neurogenic tumors were located in the paravertebral column, accounting for 90.3% (65/72) of the tumors in this region. MSCT examination could effectively distinguish benign from malignant of primary retroperitoneal tumor (sensitivity = 87.2%, specificity = 82.7%, accuracy rate = 84.5%). Malignant tumors showed more irregularity shape than benign tumor ( χ 2 = 20.468, P < .001). 82.7% (191/231) of the malignant tumors showed adhesion or even invasion of surrounding tissues and organs ( χ 2 = 23.262, P < .001). Fat density of the lipoma is uniform, and lesion is not enhanced. Liposarcoma can be seen in varying proportions of fat and soft tissue density. Conclusion: The accuracy of MSCT scan for retroperitoneal tumors is high. Meanwhile, the coincidence rate of qualitative diagnosis before operation and/or before biopsy is also high.